2016
DOI: 10.20948/prepr-2016-52
|View full text |Cite
|
Sign up to set email alerts
|

Statistical regularity of European languages and Voynich Manuscript analysis

Abstract: The statistical properties of letters frequencies in European literature texts are investigated. The determination of logarithmic dependence of letters sequence for one-language and twolanguage texts are examined. The pare of languages is suggested for Voynich Manuscript. The internal structure of Manuscript is considered. The spectral portraits of two-letters distribution are constructed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Such unusual auto correlations, pointing to the possible presence of an existing system or a memory in the process of the text creation, were also observed on various levels by many scholars: by Landini [ 13 ] on the whole manuscript sequence by using equal-symbol multiplication; by Schinner [ 14 ] on translation of the manuscript into binary sequence; by Montemurro and Zanette [ 17 ] on word use; by Vonfeld [ 18 ] on all-symbol-position sequence; and by Arutyunov et al [ 19 ] when assessing Hurst exponent on predefined symbol repetition delays. However, such an analysis–to our knowledge–has not yet been done on all individual symbols.…”
Section: Periodicity Of Symbolsmentioning
confidence: 99%
“…Such unusual auto correlations, pointing to the possible presence of an existing system or a memory in the process of the text creation, were also observed on various levels by many scholars: by Landini [ 13 ] on the whole manuscript sequence by using equal-symbol multiplication; by Schinner [ 14 ] on translation of the manuscript into binary sequence; by Montemurro and Zanette [ 17 ] on word use; by Vonfeld [ 18 ] on all-symbol-position sequence; and by Arutyunov et al [ 19 ] when assessing Hurst exponent on predefined symbol repetition delays. However, such an analysis–to our knowledge–has not yet been done on all individual symbols.…”
Section: Periodicity Of Symbolsmentioning
confidence: 99%
“…For all European languages the area of the spectrum is approximately limited by the circle with the radius 0.2 (the green region is shown on the Fig.19 and Fig.20). According to the paper [1] the area of the spectrum for the texts with the full alphabet has the form not of a circle but of an ellipse with semimajor axis equal to approximately 0.5 and semiminor axis still equal to 0.2.…”
Section: Spectral Portrait Of Voynich Manuscriptmentioning
confidence: 99%
“…This example shows that the preservation of determination of the languages mixture is not a necessary and sufficient condition for their affinity. In [1] and [2] it is shown that the full distribution of symbols depends on professional texts specifics. Nuances between different texts are unimportant, determination level fluctuates at around 0.96 and difference between actual distributions and model dependency (1) changes with the range of 0.09-0.13, that approximately coincides with similar characteristics of literary texts.…”
Section: Two-languages Symbols Statisticsmentioning
confidence: 99%
See 2 more Smart Citations